PENGARUH PEMBERIAN PUPUK HAYATI CAIR ULTRA GEN DAN PUPUK MAJEMUK NPK MAHKOTA (12-12-17-2) TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Rian Jura Arrazi; Agam Ihsan Hereri; Erida Nurahmi (Universitas Teuku Umar, 2020)
This study aims to determine the effect of the concentration of ultra gene liquid biofertilizers and crowns compound NPK and to find out whether there is any interaction between the both of it on the growth of oil palm seedlings.This research was carried out at the main nursery land of Nusantara I Plantation Limited Company (PTPN I) Kebun Baru, Langsa City, Aceh Province from June to September 2017. This study used factorial randomized block design with 16 treatments repeated 3 times. This study consisted of two factors, namely the dose of ultra gene liquid biofertilizer 0.100, 200 and 300 ml and the dose of crowns compound NPK fertilizer 0,5,10 and 15 g. The results showed that the dose of Ultra Gen liquid biofertilizer significantly affected the stem diameter, leaf number and leaf area in almost all MSP and significantly affected the leaf area of 6 MSP. The dose of Ultra Gen liquid biofertilizer treatment has a very significant effect on the growth of oil palm seedlings, which is indicated by the parameters of the increase in stem diameter, number of leaves and leaf area, and only a significant effect on leaf area 6 weeks after observation. The dose of 200 ml of the Ultra Gen factor shows better growth than other doses. There is a real interaction on seedling growth as indicated by the parameters of the number of seedlings. The highest number of seed leaves was shown by the treatment of 100 ml / polybag ultra gen with NPK 5g/polybag (U1N1), and 200 ml / polybag with no NPK fertilization (U2N0), although not significantly different from the U0N0 and U3N3 treatment combinations, but significantly different with the combination of other treatments. Keywords: crowns NPK, oil palm seeds, ultra gene liquid biofertilizers